Cognitive function immediately after maximal exercise - Sudo, M.; Komiyama, T.; Aoyagi, R.; Higaki, Y.; Nagamatsu, T.; Ando, S. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction Cognitive function is fundamentally important to most human activities. In many sports, high-level cognitive function is required under psychological and physiological stress. Increasing evidence suggests that cognitive function improves during a single bout of moderate exercise (Brisswalter et al. 2002; McMorris et al. 2011). However, little is known about how cognitive function is altered by psychological as well as physiological states immediately after exhaustive exercise. The purpose of this study was to examine the association between cognitive function and mood state immediately after exhaustive exercise. Methods: Ten participants performed a cognitive tas at rest and immediately after maximal exercise. Cognitive function was assessed with a combination of a Spatial Delayed Response task (working memory) and a Go/No-Go task (executive function). We used accuracy of the cognitive task and reaction time in the Go trial to evaluate cognitive function. We examined the association between cognitive function and mood state (pleasure, relaxation, and anxiety) immediately after exercise. Results: Maximal oxygen uptake was 49.0 ± 4.8 ml/min/kg. One participant was not able to complete the cognitive task due to exhaustion. Accuracy of the cognitive task was 90.0 ± 5.5 % at rest and 85.0 ± 12.0 % after exercise. Reaction time in the Go trials was 882 ± 331 ms at rest and 810 ± 222 ms after exercise. Delta reaction time tended to be negatively correlated with the decrease in relaxation state (p = 0.06). Discussion: Both accuracy of the cognitive task and reaction time in the Go trials slightly decreased immediately after maximal exercise. However, we did not observe significant differences, probably due to the large inter-individual differences. Given the association between cognitive function and relaxation state, the present results suggest that cognitive function and mood state may be mutually interactive under fatiguing condition. Cognitive function seems to be affected by multiple factors including psychological state.